Nine-segment laminectomy is safe for the resection of a schwannoma extending from C-2 to T-3: a rare case report (Faculty of Medicine Universitas Indonesia, 2020)
Cervical spine schwannoma, which is long and entirely intracanal, is rare to be found. Its rarity and atypical feature leads to difficulty in diagnosing and managing cases because of the scarcity of available literature. The surgical removal of this type of schwannomas via multisegment laminectomy is a great challenge because of various risks of postoperative complications. This report describes cervical spine schwannoma that was initially was not suspected as schwannoma and was subject to surgical removal via nine-segment laminectomy. In one year after surgery, motor function returned to normal strength, no new neurological deficits occurred, and no kyphotic deformity, which is a common complication of multisegment laminectomy.